Terapi Opioid pada Kasus COVID-19 - Jufan, Akhmad Yun; Kurniawaty, Juni; Dewi, Baiq Dessy Resmana (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
One-third of COVID-19 patients experience a variety of neurological symptoms involving the central and peripheral nervous systems. These symptoms include headache, dizziness, loss of consciousness, impaired smell, neuralgia, and skeletal muscle damage. Myalgia is the most common symptom in cases of COVID-19. Therefore, adequate pain management isneeded, one of the choices is using opioids. Opioid receptor agonists are a group of drugs that stimulate opioid receptors and produce their effects by mimicking endogenous opioid peptides known as endorphins.